Unfolding a peatland’s story: Assessing the restoration outcomes and driving factors from a disturbed minerotrophic peatland in Eastern Canada - Khan, Aamir Shehzad; Guêné-Nanchen, Mélina; Rochefort, Line (Ecological engineering, 2025)
The peatland restoration method, the Moss Layer Transfer Technique (MLTT), has been successfully developed and implemented to restore Sphagnum-dominated peatlands in North America. The efficiency of an adapted version of the MLTT using fen plants for minerotrophic (fen) peatland restoration has shown mixed results, especially regarding the recovery of bryophytes. Additionally, due to differences in peat extraction histories, disturbances, restoration techniques, and desired ecological outcomes, European approaches cannot be directly applied to North American peatlands. It has been suggested that active rewetting alone could ensure fen plant regeneration post-restoration. As there is a growing interest in the minerotrophic peatland restoration, fen restoration methods after peat extraction needs to be refined, and the management process stands in need of new approaches. This study presents the first case of an ecosystem-scale fen restoration project in Canada at an industrial peat extraction site. It was restored in the province of Quebec in 2009, testing three different restoration approaches, including active rewetting only – REW, active rewetting, and peat profiling with vegetation removal – REW + PRO, and a combination of active rewetting, peat profiling with vegetation removal, plus mechanical reintroduction of fen plant material (MLTT) – REW + PRO + PLANT. This study aims to compare the pre- and post-restoration (13 years) plant communities using a BACI design (Before and After Control Impact). It focuses on the recovery of bryophyte carpets and evaluates the return of fen species as well as peatland generalists, marsh-swamps, and upland species. At the whole site level, the rewetting action had a prominent impact and major success in terms of an increase in the richness and frequency of peatland vascular plant species, but the recruitment of peatland bryophytes and particularly brown mosses was relatively much less successful. Active rewetting proved relatively practicable compared to the other two restoration methods, but to enhance its efficiency, it should not result in flooding, which could subsequently lead to helophytisation. The different vegetation outcomes of the restoration were influenced by governing factors such as processes associated with restoration methods (e.g., rewetting, pre-existing vegetation removal, and donor material reintroduction) and site-specific physio-chemical and environmental conditions. Our 13 years post-restoration surveys highlight that there are still large knowledge gaps and that increased, robust research into fen restoration is needed. [Display omitted] •First Canadian ecosystem-scale fen restoration project at an industrial peat extraction site.•Application of three restoration methods, including the Fen Moss Layer Transfer Technique.•Site environmental heterogeneity was one of the driving factors for restoration success.•Vascular plants established successfully post-restoration compared to bryophytes.•Low helophyte presence and no flooding are key to effective rewetting.